Pemanfaatan Twitter Sebagai Media Promosi Terhadap UMKM - Besti Tiurmaida Pardede; Ririsma Sihombing; Sherly Prissillia Devi; Chandra Bayu Hidayat (Journal Of Business, Finance, and Economics (JBFE), 2022)
This study examines how the influence of the use of social media Twitter in promoting small businesses (MSMEs). This research uses a literature study by reviewing previous research. This study uses a qualitative method with data processing using a literature review. The results obtained from this study indicate that the use of social media twitter has a fairly high and positive influence in promoting the MSME business, with the easy twitter feature and tapa budget being the choice of MSME businessme.